Constitutional Framework, Governance Gaps and Corporate Risk Management in Long-Term Care in Finland - Vartiainen, Alexis (My University, 2023)
The fundamental rights and constitutional reform implemented in the 1990s strengthened the rights of every person under Finnish jurisdiction. However, in some social welfare services, such as long-term care, situations emerge where people's fundamental rights are restricted without an acceptable reason stated in law. Concurrently, administrative reforms following New Public Management principles were carried out by the government, the purpose of which were to increase the effectiveness of financial steering in service provision. As a result of the reforms, service provision that has key fundamental rights impacts was transferred outside the public sector confines of the Constitution and given to private companies. Many provisions of the Constitution are not fully regulated in law, which means that the existence of governance gaps cannot be completely avoided. Especially after the nursing care scandal in 2019, the regulator has attempted to address some of these shortcomings. The thesis examines the minimum content of the concept of corporate social responsibility as understood through the purpose of a limited liability company under Finnish company law. This is then compared to the requirements of the Constitution regarding respect for fundamental rights. The study finds that where the intent of the legislator is clear, but material legislation is incomplete, it is up to the company's operative decision-making to respect fundamental rights. Recently enacted legislative reforms indicate that the wiggle-room left by the legislator cannot be abused without negative effects on market conditions. The main conclusion of the study is that the fundamental rights obligations imposed by the Constitution on the government will become a key market factor for companies acting as service providers for the public sector. By adapting to the fundamental rights requirements on a self-guiding basis, companies can mitigate and prevent fundamental rights violations. This in turn will make it less likely that the legislator will interfere in business and market conditions. To effectively steer and monitor their actions, companies can employ corporate social responsibility tools, such as human rights due diligence. From the legislator's point of view, this will also improve the steering of service production without jeopardizing provider competition and the potential benefits that can be extracted from competition. At the end of the thesis, policy proposals de lege ferenda are provided for future discussion and research. The study is legal dogmatic in nature. The questions are examined by means of practical legal doctrine. Law and economics arguments are utilized as material sources in accordance with the traditional doctrine on use of legal sources. Using key literature from the fields corporate law, constitutional law and international law, the study aims to integrate concepts and tools familiar from the field of international corporate social responsibility into domestic legal research, especially regarding the service sector and more specifically social services.

1990-luvulla toteutettu perusoikeus- ja perustuslakiuudistus vahvisti jokaisen Suomen lainkäyttöalueella olevan henkilön oikeuksia. Eräissä sosiaalihuollon palveluissa kuten ympärivuorokautisessa palveluasumisessa esiintyy kuitenkin edelleen tilanteita, joissa ihmisten perusoikeuksia rajoitetaan ilman laista ilmenevää hyväksyttävää syytä. Samanaikaisesti 1990-luvulla toteutettiin uuden julkisjohtamisen opin mukaisia hallinnollisia reformeja, joiden tarkoituksena oli lisätä talousohjauksen vaikuttavuutta palvelutuotannossa ulkoistamalla toimintoja yksityisten yhtiöiden hoidettaviksi. Uudistusten myötä perustuslain vaikutusalueen ulkopuolelle siirrettiin sellaista palvelutuotantoa, jolla on keskeisiä perusoikeusvaikutuksia. Monia perustuslain määräyksiä ei ole säännelty tyhjentävästi, minkä takia lainsäädännöllisten aukkojen (governance gap) esiintymistä ei voi täysin välttää. Erityisesti vuoden 2019 hoivaskandaalin jälkeen lainsäätäjä on kuitenkin pyrkinyt puuttumaan havaittuihin epäkohtiin. Tutkielmassa selvitetään yritysvastuukäsitteen ja osakeyhtiön tarkoituksen minimisisältö osakeyhtiölain (624/2006) kontekstissa, joita peilataan perustuslain vaatimuksiin perusoikeuksien kunnioittamisen osalta. Lainsäätäjän tahdon ollessa selkeä, mutta erityislainsäädännön ollessa vaillinainen, jää palveluja tuottavan osakeyhtiön operatiivisen päätöksenteon varaan kunnioittaa perusoikeuksia perustuslain tarkoittamalla tavalla. Viime vuosien lainsäädäntöhankkeet kuitenkin viittaavat siihen, että lainsäätäjän yhtiöille jättämää liikkumatilaa ei voi väärinkäyttää ilman kielteisiä vaikutuksia yhtiöiden toimintaympäristölle. Tutkimuksen keskeinen johtopäätös on, että perustuslain julkiselle sektorille asettamista perusoikeusvelvoitteista muodostuu keskeinen markkinatekijä yhtiöille, jotka toimivat julkisen sektorin palvelutuottajina. Sopeutumalla määräyksiin omatoimisesti yhtiöt ehkäisevät perusoikeusrikkomuksia ja niistä johtuvia lainsäädäntöhankkeita, joita vuoden 2019 skandaalin jälkeen on nähty. Toimintansa ohjaamiseksi yhtiöt voivat hyödyntää yritysvastuutyökaluja, kuten ihmisoikeuskeskeisen asianmukaisen huolellisuuden periaatetta (human rights due diligence). Lainsäätäjän näkökulmasta tämä tehostaa palvelutuotantoyhtiöiden ohjausta palvelutuotantokilpailua ja siitä potentiaalisesti saatavia hyötyjä vaarantamatta. Tutkielman lopussa annetaan konkreettisia ehdotuksia de lege ferenda millaisia työkaluja sosiaalipalveluiden tuotannossa voisi ottaa käyttöön. Tutkimus on luonteeltaan oikeusdogmaattinen. Kysymyksiä tarkastellaan käytännöllisen lainopin keinoin. Keskeisiä yhtiöoikeudellisia, valtiosääntöoikeudellisia ja kansainvälisen oikeuden lähteitä käyttäen tutkimus pyrkii integroimaan yritysvastuusääntelyn kentältä tuttuja konsepteja ja työkaluja kotimaiseen oikeudelliseen tutkimukseen erityisesti palvelualojen ja tarkemmin sosiaalipalvelujen alalle. Oikeustaloustieteellisiä argumentteja hyödynnetään perinteisen oikeuslähdeopin mukaisesti reaalisina argumentteina.
Keywords: kestävä liiketoiminta, oikeustiede, osakeyhtiöt, perusoikeudet, perustuslainmukaisuus, sosiaalipalvelut, sote-palvelut, sote-uudistus, tehostettu palveluasuminen, terveyspalvelut, yhteiskuntavastuu, yhtiöoikeus, ympärivuorokautinen palveluasuminen, yritysvastuu